Light-matter interactions in atomically thin transition metal dichalcogenides - Zhao, Jiaxin (Nanyang Technological University, 2021)
Monolayer group VI transition metal dichalcogenides (TMDs) are emerging two-dimensional (2D) semiconductors with a sizable direct bandgap and exceptional physical properties. The tightly bound excitons with giant oscillator strength render monolayer TMDs as an ideal platform to investigate light-matter interactions when they are integrated with optical microcavities. By coherently superimposing excitons and cavity photons, the exciton-polaritons based on monolayer TMDs are stable at room temperature with considerable promise towards optoelectronic and valleytronic devices. In this thesis, I mainly focus on investigations on light-matter interactions in monolayer TMDs and microcavities. Fundamental understandings on the dynamics of charge carrier and excitonic quasiparticles in monolayer are of central significant for optoelectronic and photonic applications. In Chapter 3, we start with investigations on the carrier dynamics and many-body interactions in monolayer TMDs by employing transient absorption spectroscopy. As for monolayer tungsten disulphide (WS2), the exciton energy renormalization is revealed with a distinct red-blue-red shift upon above-bandgap optical excitations. The physical processes in these three typical time regimes are dominated by free carrier screening effect, Coulombic exciton-exciton interactions and Auger photocarrier generation, respectively. An intrinsic exciton radiative lifetime around 1.2 picoseconds (ps) is shown at low temperature. Because of the efficient Auger nonradiative decay of both bright and dark excitons, the system is in a nonequilibrium state at longer time regime (around nanosecond timescale). In addition, the dynamics of charged excitons (trions) is observed to be different from that of excitons that the radiative lifetime of trions is around 108.7 ps at low excitation densities. These findings elucidate the dynamics of excitonic quasiparticles and intricate many-body physics in the 2D semiconductors. By integrating plasmonic nanostructures with TMDs monolayers, this coupled system provides a highly unexplored territory towards understanding the intermediate exciton-plasmon coupling regime. In Chapter 4, utilizing the ultrafast femtosecond (fs) pump-probe spectroscopy, we investigate the exciton-plasmon coupling in a monolayer WS2-Ag nanodisk hybrid system which shows a Fano resonance at the steady-state regime. With upon the pump excitation, we observe the instant switch-off of the Fano resonance, characterized by the photo-induced absorption signal at the Fano resonance frequency. The fast and slow recovery processes are revealed. Because of the energy transfer from excitons of WS2 to plasmons in Ag nanodisks, the system shows the fast recovery of the Fano resonance which starts at the sub-100 fs timescale. Following the carrier relaxation in the systems, the slow recovery process lasts for several tens of ps. By coherently superimposing monolayer exciton and cavity photons, when the system is in the strong coupling regime, the formation of exciton polaritons potentially harnesses the valley-polarized polariton-polariton interactions for novel valleytronic devices. In additional, as half-light, half-matter bosonic quasiparticles, polaritons can condense into a single quantum state with spontaneous coherence at ultralow threshold, which is crucial for the developments of quantum technology. In Chapter 5, we demonstrate the realization of polariton condensation in monolayer WS2 microcavity at room temperature. The system working in the strong coupling regime exhibits a clear anti-crossing behavior with a large Rabi splitting around 37 meV. The continuous-wave pumped exciton-polaritons condensation and lasing with ultralow thresholds is evidenced by the macroscopic occupation of the ground state, that undergoes a nonlinear increase of the emission and a continuous blueshift, a build-up of spatial coherence, and a detuning-controlled threshold. Our work presents a critically important step towards exploiting nonlinear polariton–polariton interactions and polaritonic devices with valley functionality at room temperature. Furthermore, the layered materials can be stacked vertically to fabricate van der Waals heterostructures, which enable new strategies for manipulation of light-matter interactions in the strong coupling regime. In Chapter 6, we incorporate different number of WS2 monolayers separated by silicon dioxide (SiO2) layers to form multiple quantum-wells (QWs) structures within a planar microcavity. The strong coupling between the excitons in quantum wells and the cavity photons is evidenced by the formation of polariton branches with a clear anti-crossing between the cavity mode and the neutral exciton energy at room temperature. The vacuum Rabi splitting is enhanced to 52 meV in double and 72 meV in quadruple QW microcavities, respectively. In additional, we report a new valley polariton strategy based on the quadruple QW microcavity as an example. Overall, our results in this thesis present a comprehensive physical picture of the distinct exciton dynamics and many-body interactions in monolayer TMDs. Furthermore, because of the unique physical properties, the robust polaritons based on the monolayer TMDs pave the way for manipulating the light matter interactions and present a critical step towards the practical utilization of polaritonic devices with valley functionality.